2019
DOI: 10.1590/0102-33062018abb0288
|View full text |Cite
|
Sign up to set email alerts
|

Global warming decreases the morphological traits of germination and environmental suitability of Dipteryx alata (Fabaceae) in Brazilian Cerrado

Abstract: We experimentally evaluated how different temperatures affect germination of individual seedlings of Dipteryx alata, and estimated the impact of climate change on the species using ecological niche modeling. A total of 240 seeds were randomly distributed among three different temperature treatments (32 ºC, 36 ºC, and 40 ºC), and monitored for 35 days. We measured seven seed traits and estimated the ecological niche of D. alata using a consensus of four methods. The treatment with the highest temperature produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
0
0
1
Order By: Relevance
“…Ribeiro et al [52] showed significant impacts of climate change on the environmental suitability of Dipteryx alata Vogel in the Brazilian Cerrado. Similar results have been reported in other studies of plants species from the Cerrado, related to climate change's impacts [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro et al [52] showed significant impacts of climate change on the environmental suitability of Dipteryx alata Vogel in the Brazilian Cerrado. Similar results have been reported in other studies of plants species from the Cerrado, related to climate change's impacts [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al [52] showed significant impacts of climate change on the environmental suitability of Dipteryx alata Vogel in the Brazilian Cerrado. Similar results have been reported in other studies of plants species from the Cerrado, related to climate change's impacts [52][53][54]. However, despite these studies demonstrating negative effects on the distribution of plants in this biome, Tomaz et al [55] indicated that a medicinal plant species tends to adapt in different environmental conditions, since the distribution of the species tends to decrease in the Atlantic Forest and Caatinga over northeast Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…É comum na literatura trabalhos que reportam frequências de irrigação e frações de reposição diversas, com variação de uma irrigação diária até doze vezes ao dia em espécies distintas [10,16,17,18,19] entretanto, torna-se inviável uma frequência reduzida associada ao uso de hidrogel, pois, segundo [20] o custo de produção e plantio com uso do hidrogel é menor em estações secas. Ou seja, na produção de mudas em substratos comerciais, parece inconsistente o uso de doses de polímero hidroabsorvente com irrigações frequentes ou diárias visando manter a umidade elevada.…”
Section: Introductionunclassified